2018
DOI: 10.1038/s41467-018-06179-0
|View full text |Cite
|
Sign up to set email alerts
|

A small molecule targeting myoferlin exerts promising anti-tumor effects on breast cancer

Abstract: Breast cancer is one of the most lethal cancers in women when it reaches the metastatic stage. Here, we screen a library of small molecules for inhibitors of breast cancer cell invasion, and use structure/activity relationship studies to develop a series of small molecules with improved activity. We find WJ460 as one of the lead compounds exerting anti-metastatic activity in the nanomolar range in breast cancer cells. Proteomic and biochemical studies identify myoferlin (MYOF) as the direct target of WJ460. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 41 publications
2
58
0
Order By: Relevance
“…Tumor metastasis is a multistep process involving metastasis formation and colonization. Approximately one-third of BC patients harbor metastases in lymph nodes at the time of surgery, which highlights the necessity for drugs targeting metastatic colonization 39 . Our work found that NBT impeded BC and LC cell migration and extravasation into the lung parenchyma, thereby revealing a potential capacity to inhibit the formation of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metastasis is a multistep process involving metastasis formation and colonization. Approximately one-third of BC patients harbor metastases in lymph nodes at the time of surgery, which highlights the necessity for drugs targeting metastatic colonization 39 . Our work found that NBT impeded BC and LC cell migration and extravasation into the lung parenchyma, thereby revealing a potential capacity to inhibit the formation of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer (BC) is the most frequently diagnosed cancer and the leading cause of cancer-related mortality among women worldwide (1,2). Despite the improved prognosis of individuals with BC and advances in radical surgery along with adjuvant therapy (3,4), BC is associated with common recurrence and persistently high mortality rates. BC frequently leads to multi-organ distant metastasis, such as in the lung, bone, liver, and brain (5).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mitofusin-2 is a member of the dynamin-like GTPase superfamily and harbors a proline-rich domain [30] when myoferlin contains a SH3 domain [31] controlling protein-protein interactions through proline-rich domains. It is worth noting that a myoferlin colocalization with rab7 GTPase was reported in late endosomes [19], and a direct interaction was suggested in an exogenous expression system [32]. Myoferlin exhibits several additional domains (FerB, FerI, Ferlin C, DysF) with an unidentified function [9], opening new possibilities for its interaction with mitochondrial mitofusins, including mitofusin-1.…”
Section: Discussionmentioning
confidence: 94%